Politics of welfare : comparisons across Indian states - Tillin, Louise; Deshpande, Rajeshwari; Kailash, K. K.; Lokniti (New Delhi, India) (New Delhi Oxford, 2018)
Contributed articles.
"The seeds for the research on which this volume is based were sown at a workshop on comparative state politics, organized by the Lokniti Programme for Comparative Democracy at the Centre for study of Developing Societies (CSDS), Delhi, in January 2011."--Acknowledgements.
Keywords: Public welfare